Microplastic polymers in shellfish and fish in the coastal area - S. Basri K.; A. Daud; A.B. Birawida; M. Maming; H.J. Mukono; D.S. Arsyad (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVE: The coastal area of Jeneponto Regency, South Sulawesi, Indonesia, is heavily impacted by microplastic pollution, which poses a threat to marine organisms such as shellfish and fish. This aim of this study was to identifiy the presence of microplastic polymers, including vinylidene chloride, polyacetylene, polychlorotrifluoroethylene, polybutylene terephthalate, poly(isobutyl methacrylate), cellulose acetate butyrate, polybutadiene, and polyvinylchloride, in shellfish and fish in the coastal area of Jeneponto district, Indonesia.METHODS: In total, 60 shellfish and fish samples were collected directly from 12 locations in the coastal waters of Jeneponto Regency. Sample preparation, including enzymatic digestion and mechanical destruction, was performed to separate the organic tissues of fish and shellfish into small particles. Optical microscopy (at 100× and 400× magnification) was used to observe the morphology and to count the number of particles per sample volume using a modified Neubeuer Improved Counting Chamber. Fourier-transform infrared spectroscopy was used to determine the type of polymer.FINDING: Feather clams contained the highest number of microplastics, with a total of 58 items ranging from 0.027 to 4.587 millimeters in size. The total abundance of microplastics in feather clams ranged from 0.25 to 2.14 items per gram. Kurisi fish contained 22 items ranging from 0.085 to 2.127 millimeters in size, with a total abundance ranging from 0.01 to 0.08 items per gram. The types of polymers identified in the fish and clams included vinylidene chloride, polyacetylene, polychlorotrifluoroethylene, polybutylene terephthalate, poly(isobutyl methacrylate), cellulose acetate butyrate, polybutadiene, and polyvinyl chloride. Vinylidene chloride was the predominant type of microplastic polymer, accounting for 42 percent of all microplastic polymers.CONCLUSION: This study successfully identified eight types of microplastic polymers found in shellfish and fish in the coastal area of Jeneponto; the most common was vinylidene chloride. These findings indicate that marine organisms and humans are exposed to microplastics, which are potentially harmful, but further research is needed to understand the full extent of the associated environmental health impacts and risks.